2022
DOI: 10.1021/acsomega.2c05670
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Optimization of CrOOH/rGO-Based Electrode Material for a Highly Efficient Supercapacitor Device

Abstract: New electrode materials for supercapacitor devices are the primary focus of current research into energy-storage devices. Besides, exact control of the proportions of these new materials while forming electrodes for coin cell supercapacitor devices is very important for the large-scale manufacturing or at industrial scale. Here we report a facile synthesis of CrOOH with ascorbic acid and explore an exact composition with reduced graphene oxide to achieve a highly efficient electrode material for supercapacitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The working electrode was prepared by forming a paste of active material (NiMOF), commercial grade activated charcoal (AC), poly(vinylidene fluoride) (PVDF) as a binder, and 1-methyl-2-pyrrolidone as a solvent, by maintaining a proportion of active material:AC:binder = 6:3:1, respectively. A higher proportion of AC is utilized as the active material, being a MOF, is a poor conductor; however, this proportion is also reported in various articles [22,23]. Nevertheless, it also refers to the electrode material containing a lower percentage of active material which can increase the performance if a suitable conductor is utilized with the optimum ratio, or the composites of MOFs are formed with some conducting materials.…”
Section: Electrochemical Characterization 241 Electrode Preparationmentioning
confidence: 99%
“…The working electrode was prepared by forming a paste of active material (NiMOF), commercial grade activated charcoal (AC), poly(vinylidene fluoride) (PVDF) as a binder, and 1-methyl-2-pyrrolidone as a solvent, by maintaining a proportion of active material:AC:binder = 6:3:1, respectively. A higher proportion of AC is utilized as the active material, being a MOF, is a poor conductor; however, this proportion is also reported in various articles [22,23]. Nevertheless, it also refers to the electrode material containing a lower percentage of active material which can increase the performance if a suitable conductor is utilized with the optimum ratio, or the composites of MOFs are formed with some conducting materials.…”
Section: Electrochemical Characterization 241 Electrode Preparationmentioning
confidence: 99%
“…Pseudocapacitive materials store charge by redox (Faradaic) reactions in the presence of an electrolyte . Similar to electrical double-layer capacitance, pseudocapacitance is also an ultrafast mechanism. Various materials, including transition metal oxides, MXenes, conductive polymers, and redox organic molecules, have been widely studied as pseudocapacitive electrode materials. Particularly, quinones and their derivatives can be employed for supercapacitor applications owing to their intrinsic electrochemical redox activity. These organic molecules have controllable structures that can be tuned by modifying the number of aromatic groups and changing the identity and location of their attached functional groups. , The organic backbones of these molecules are stable when undergoing Faradaic reactions, experiencing minimal structural changes, unlike metal oxides. Furthermore, Wedege et al showed that using quinones for application in energy storage devices is economically feasible.…”
Section: Introductionmentioning
confidence: 99%
“… 25 27 Various materials, including transition metal oxides, MXenes, conductive polymers, and redox organic molecules, have been widely studied as pseudocapacitive electrode materials. 28 34 Particularly, quinones and their derivatives can be employed for supercapacitor applications owing to their intrinsic electrochemical redox activity. 35 38 These organic molecules have controllable structures that can be tuned by modifying the number of aromatic groups and changing the identity and location of their attached functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of supercapacitive materials is driven by their electrochemical performance. These materials can be broadly categorized into electric double-layer capacitors (EDLC) and pseudocapacitors based on their charge storage mechanisms. , Pseudocapacitor materials, including transition metal oxides (TMOs) and conducting polymers (CPs), exhibit higher specific capacitance and energy density values compared to carbon-based EDLC materials, thanks to their faradaic reactions. Among CPs, polyaniline (PANI) stands out as a promising electrode material for SCs due to its relatively high conductivity, environmental stability, low cost, and ease of synthesis. , However, the cyclic life of PANI is limited when used solely as an electrode material, as it undergoes structural degradation during continuous doping and dedoping of ions between the electrode and electrolyte . This limitation can be overcome by creating a suitable composite of PANI with other materials that possess superior supercapacitive properties. , …”
Section: Introductionmentioning
confidence: 99%